KESIAPSIAGAAN DENGAN PERAN PERAWAT DALAM MANAJEMEN PRA BENCANA DI PUSKESMAS TIBAWA KABUPATEN GORONTALO - Pipin Yunus; Haslinda Damansyah; Arrizka R Saleh (Universitas Muhammadiyah Gorontalo, 2020)
Preparedness is the activities that implemented to anticipate disaster through organization also through appropriate and efficient steps. The role of nurse is as the health service officers, manager of nursing services, and in educational institutions as educators, researchers, and nursing developers. The objective of research was to determine the relationship between preparedness with the role of nurses in pre-disaster management at Tibawa health centre. The method is Cross Sectional research with correlation research design. The samples are 21 respondents. The instrument used questionnaire and interviews. Technique of analysis data used chi square test. The result showed the nurse’s preparedness with ready category with less of nurse’s roles are 3 respondents and good roles are 8 respondents (38,1 %) while nurse’s preparedness with less ready of nurse’s roles are 9 respondents (28,6 %) and good roles are 4 respondents (19,0 %). Chi square result obtained fisher exact value was 0,001 or ρ value < α 0,05.